Stem Cell Therapy in Limb Ischemia: State-of-Art, Perspective, and Possible Impacts of Endometrial-Derived Stem Cells - Khodayari, Saeed; Khodayari, Hamid; Ebrahimi-Barough, Somayeh; Khanmohammadi, Mehdi; Islam, Md Shahidul; Vesovic, Miko; Goodarzi, Arash; Mahmoodzadeh, Habibollah; Nayernia, Karim; Aghdami, Nasser; Ai, Jafar (Frontiers in Cell and Developmental Biology, 2022)
Abstract As an evidence-based performance, the rising incidence of various ischemic disorders has been observed across many nations. As a result, there is a growing need for the development of more effective regenerative approaches that could serve as main therapeutic strategies for the treatment of these diseases. From a cellular perspective, promoted complex inflammatory mechanisms, after inhibition of organ blood flow, can lead to cell death in all tissue types. In this case, using stem cell technology provides a safe and regenerative approach for the ischemic tissue revascularization and functional cell formation. Limb ischemia (LI) is one of the most frequent ischemic disease types, and has been shown to have a promising regenerative response through stem cell therapy based on several clinical trials. Bone marrow-derived mononuclear cells (BM-MNCs), peripheral blood CD34-positive mononuclear cells (CD34+ PB-MNCs), mesenchymal stem cells (MSCs), and endothelial stem/progenitor cells (ESPCs) are the main, well-examined stem cell types in these studies. Additionally, our investigations reveal that endometrial tissue can be considered as a suitable candidate for isolating new safe, effective, and feasible multipotent stem cells for limb regeneration. In addition to other team’s results, our in-depth studies on endometrial-derived stem cells (EnSCs) have shown that these cells have translational potential for limb ischemia treatment. The EnSCs are able to generate diverse types of cells which are essential for limb reconstruction, including the endothelial cells, smooth muscle cells, muscle cells, and even peripheral nervous system populations. Hence, the main object of this review is to present stem cell technology and evaluate its method of regeneration on ischemic limb tissue.